2018
DOI: 10.20944/preprints201808.0172.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low infection of Phelipanche aegyptiaca in Micro-Tom mutants deficient in CAROTENOID CLEAVAGE DIOXYGENASE 8

Abstract: Strigolactones (SLs), a group of plant hormones, induce germination of root-parasitic plants and inhibit shoot branching in many plants. Shoot branching is an important trait that affects the number and quality of flowers and fruits. Root-parasitic plants such as Phelipanche spp. infect tomato roots and cause economic damage in Europe and North Africa. Thus, resistant tomato cultivars are needed. In this study, we found carotenoid cleavage dioxygenase 8-defective mutants of Micro-Tom tomato (slccd8) by the "ta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…SlCYP722C-KO plants did not show the prominent phenotypes of the SL-deficient mutant Slccd8, such as increased shoot branching and reduced stem length (Fig. 6, B to D) (23). Methyl carlactonoate (MeCLA) is known to potentially function as an active hormone that inhibits shoot branching in Arabidopsis (14); however, MeCLA was undetectable in root exudates and root and shoot extracts in SlCYP722C-KO plants, and it was unclear whether MeCLA contributes to the regulation of plant architecture in SlCYP722C-KO plants ( fig.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…SlCYP722C-KO plants did not show the prominent phenotypes of the SL-deficient mutant Slccd8, such as increased shoot branching and reduced stem length (Fig. 6, B to D) (23). Methyl carlactonoate (MeCLA) is known to potentially function as an active hormone that inhibits shoot branching in Arabidopsis (14); however, MeCLA was undetectable in root exudates and root and shoot extracts in SlCYP722C-KO plants, and it was unclear whether MeCLA contributes to the regulation of plant architecture in SlCYP722C-KO plants ( fig.…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, CYP722C-KO plants have the potential to combat noxious root parasitic weeds. SlCYP722C-KO plants reduce the germination of P. aegyptiaca, a serious constraint on tomato production (23,24), without changing the plant architecture, and they release CLA from the roots. The activity of CLA against the hyphal branching of AMF was comparable with that of natural canonical SLs such as strigol and sorgomol (25), suggesting that CLA can be used as a signaling molecule to facilitate symbiotic interactions with AMF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Grafting experiments in pea (Beveridge et al, 2000) and tomato (Hasegawa et al, 2018) showed that root‐synthesised SLs could phenotypically revert the branching phenotype of SL‐deficient shoots, indicating acropetal SL transport from the root. Unlike ABA, SL transport is unidirectional with no evidence of basipetal transport of SL from the shoot to the root (Kameoka & Kyozuka, 2018).…”
Section: Abscisic Acidmentioning
confidence: 99%